Efficacy and Safety of Ceftazidime-Avibactam Plus Metronidazole Versus Meropenem in the Treatment of Complicated Intra-abdominal Infection: Results From a Randomized, Controlled, Double-Blind, Phase 3 Program - Mazuski, John E. (Clin Infect Dis, 2016)
Background. When combined with ceftazidime, the novel non–β-lactam β-lactamase inhibitor avibactam provides a carbapenem alternative against multidrug-resistant infections. Efficacy and safety of ceftazidime-avibactam plus metronidazole were compared with meropenem in 1066 men and women with complicated intra-abdominal infections from 2 identical, randomized, double-blind phase 3 studies (NCT01499290 and NCT01500239). Methods. The primary end point was clinical cure at test-of-cure visit 28–35 days after randomization, assessed by noninferiority of ceftazidime-avibactam plus metronidazole to meropenem in the microbiologically modified intention-to-treat (mMITT) population (in accordance with US Food and Drug Administration guidance), and the modified intention-to-treat and clinically evaluable populations (European Medicines Agency guidance). Noninferiority was considered met if the lower limit of the 95% confidence interval for between-group difference was greater than the prespecified noninferiority margin of −12.5%. Results. Ceftazidime-avibactam plus metronidazole was noninferior to meropenem across all primary analysis populations. Clinical cure rates with ceftazidime-avibactam plus metronidazole and meropenem, respectively, were as follows: mMITT population, 81.6% and 85.1% (between-group difference, −3.5%; 95% confidence interval −8.64 to 1.58); modified intention-to-treat, 82.5% and 84.9% (−2.4%; −6.90 to 2.10); and clinically evaluable, 91.7% and 92.5% (−0.8%; −4.61 to 2.89). The clinical cure rate with ceftazidime-avibactam plus metronidazole for ceftazidime-resistant infections was comparable to that with meropenem (mMITT population, 83.0% and 85.9%, respectively) and similar to the regimen's own efficacy against ceftazidime-susceptible infections (82.0%). Adverse events were similar between groups. Conclusions. Ceftazidime-avibactam plus metronidazole was noninferior to meropenem in the treatment of complicated intra-abdominal infections. Efficacy was similar against infections caused by ceftazidime-susceptible and ceftazidime-resistant pathogens. The safety profile of ceftazidime-avibactam plus metronidazole was consistent with that previously observed with ceftazidime alone. Clinical Trials Registration. NCT01499290 and NCT01500239.